Representation of Violence Against Female Characters in Indonesian Horror Novels - Joko Widodo; Hidayah Budi Qur’ani; Purwati Anggraini; Mohammad Khikam Zahidi; Mohammad Nuryasin (Riviera Publishing, 2024)
This study explores the representation of violence against female characters in Indonesian horror novels, examining how these portrayals reflect societal views on gender and power. By analyzing three popular novels, the research focuses on types of violence—physical, psychological, and symbolic—that female characters experience, aiming to uncover how these depictions critique patriarchal norms. Employing a descriptive qualitative approach, the study uses textual analysis alongside a feminist narrative framework to interpret recurring themes and patterns within these narratives. Findings reveal that, while female characters are often portrayed as victims, they also demonstrate moments of resistance and agency, challenging traditional roles and societal expectations. This ambivalent portrayal highlights both the vulnerability and resilience of women, offering insights into the complex dynamics of gender in Indonesian culture. The study concludes that Indonesian horror novels serve as a powerful medium for social critique, using horror to comment on issues of gender-based violence and the potential for women to disrupt oppressive structures. This research emphasizes the role of literature in reflecting and challenging societal norms, particularly regarding the representation of women.